Early onset cerebral amyloid angiopathy following childhood exposure to cadaveric dura. Issue 2 (17th January 2019) - Banerjee, Gargi; Adams, Matthew E.; Jaunmuktane, Zane; Alistair Lammie, G.; Turner, Ben; Wani, Mushtaq; Sawhney, Inder M. S.; Houlden, Henry; Mead, Simon; Brandner, Sebastian; Werring, David J.
Abstract : Amyloid‐β transmission has been described in patients both with and without iatrogenic Creutzfeldt–Jakob disease; however, there is little information regarding the clinical impact of this acquired amyloid‐β pathology during life. Here, for the first time, we describe in detail the clinical and neuroimaging findings in 3 patients with early onset symptomatic amyloid‐β cerebral amyloid angiopathy following childhood exposure to cadaveric dura (by neurosurgical grafting in 2 patients and tumor embolization in a third). Our observations provide further in vivo evidence that cerebral amyloid angiopathy might be caused by transmission of amyloid‐β seeds (prions) present in cadaveric dura and have diagnostic relevance for younger patients presenting with suspected cerebral amyloid angiopathy. Ann Neurol 2019; 1–7ANN NEUROL 2019;85:284–290.